Construction of Online Loans on Social Media Framing: Analysis of Pindar Promotion Issues in Visual and Narrative on Instagram - Defira Novianti Crisandy; Hifni Alifahmi (Journal Research of Social Science, Economics, and Management, 2025)
The development of financial technology has driven the growth of online lending (pindar) services in Indonesia, particularly among the younger generation who actively use social media platforms such as Instagram. This study aims to analyze how online lending issues are framed in promotional content by two legal service providers, AdaKami and Kredione, through visual and narrative messages on Instagram. Using a qualitative approach, this research applies framing analysis based on Gamson and Modigliani’s (1989) theory and integrates the Social Construction of Reality theory (Berger & Luckmann, 1966/1989) with the Social Construction of Technology (SCOT) framework by Trevor Pinch and Wiebe Bijker (1984). The findings reveal that the promotional framing of online lending on Instagram emphasizes ease of access, service speed, and a consumerist lifestyle as the main appeals. The study concludes that social media, particularly Instagram, plays a central role in shaping public perceptions of online loans. The normalization of digital debt practices through manipulative Instagram framing poses social risks, especially for vulnerable groups. Therefore, strategic interventions are recommended from regulators, educators, and service providers to promote more ethical digital communication and critical financial literacy.